Review: Biodiversity conservation strategy in a native perspective; case study of shifting cultivation at the Dayaks of Kalimantan - AHMAD DWI SETYAWAN (Nusantara Bioscience, 2010)
Abstract. Setyawan AD. 2010. Biodiversity conservation strategy in a native perspective; case study of shifting cultivation at the Dayaks of Kalimantan. Nusantara Bioscience 2: 97-108. Native tribes generally are original conservationists; they build genuine conservation strategy of natural resources and environment for sustainable living. Dayak is a native tribe of Kalimantan that has been living for thousands of years; they use shifting cultivation to manage the communal forest lands due to Kalimantan’s poor soil of minerals and nutrients, where the presence of phosphorus becomes a limiting factor for crops cultivation. In tropical forests, phosphorus mostly stored in the trees, so to remove it, the forest burning is carried out. Nutrients released into the soil can be used for upland rice (gogo) cultivation, until depleted; after that, cultivators need to open a forest, while the old land was abandoned (fallow) until it becomes forest again (for 20-25 years). The consecutive land clearing causes the formation of mosaics land with different succession ages and diverse biodiversity. This process is often combined with agroforestry systems (multicultural forest gardens), where the will-be-abandoned fields are planted with a variety of useful trees that can be integrated in forest ecosystems, especially rubber and fruits. These systems of shifting cultivation are often blamed as the main factor of forest degradation and fires, but in the last 300 years, this system has little impact on forest degradation. But, this is relatively low in productivity and subsistent, so it is not suitable for the modern agriculture which demands high productivity and measurable, mass and continuous yield, as well as related to the market. The increased population and industrial development of forestry, plantation, mining, etc. make the communal forest become narrower, so the fallow periods are shortened (5-15 years) and the lands are degraded into grasslands. In the future, shifting cultivation remains one of the Dayaks option to meet the needs of rice, but agroforestry should be developed because of its higher economic value.